2018
DOI: 10.12955/cbup.v6.1291
|View full text |Cite
|
Sign up to set email alerts
|

Electrotransfer of Cytokine Genes for Cancer Treatment

Abstract: Gene electrotransfer, which designates the combination of gene transfer and electroporation, is a physical method for transfecting genes into cells and tissues. Many reports for the utilization of this techniques in animals confirmed that gene electrotransfer is a safe and efficient method. One of the major advantages of electrogene therapy is that it does not result in systemic toxicity. Gene electrotransfer (GET) of plasmids encoding cytokines has been shown to generate a potent anti-tumor effect. Delivery o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 32 publications
(34 reference statements)
0
7
0
Order By: Relevance
“…Cytokine therapy in combination with electroporation has proven to be a successful and safe technique to treat cancer ( Chopra and Satkauskas, 2018 ). Specifically, therapy that utilizes electroporation and cytokines such as IL-12 can enhance the effectiveness of immunotherapy ( Kishida et al, 2001 ; Lohr et al, 2001 ; Yamashita et al, 2001 ; Heller et al, 2006 ; Cemazar et al, 2010 ) due to easier cytokine plasmid uptake and increased fragility of the cancer cells.…”
Section: Electrical Stimulation To Modulate the Immune System For Cancer Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Cytokine therapy in combination with electroporation has proven to be a successful and safe technique to treat cancer ( Chopra and Satkauskas, 2018 ). Specifically, therapy that utilizes electroporation and cytokines such as IL-12 can enhance the effectiveness of immunotherapy ( Kishida et al, 2001 ; Lohr et al, 2001 ; Yamashita et al, 2001 ; Heller et al, 2006 ; Cemazar et al, 2010 ) due to easier cytokine plasmid uptake and increased fragility of the cancer cells.…”
Section: Electrical Stimulation To Modulate the Immune System For Cancer Treatmentmentioning
confidence: 99%
“…Even though IL12 is one of the most commonly used immune cytokine for electroporation based cancer therapies, other cytokines that have also been used are other interleukins like IL 18, IL 33 and IL 15 as well as interferons like IFn-α and IFn-γ ( Chopra and Satkauskas, 2018 ). Each of these cytokines has been used for electroporation based cytokine therapy by activating production of T cells, Th1 cells differentiation, increasing antigen presentation and recruitment of dendritic cells.…”
Section: Electrical Stimulation To Modulate the Immune System For Cancer Treatmentmentioning
confidence: 99%
“…Not only has IL-12 immune cytokine shown to be effective for electroporation-based cancer therapies, but also other genes expressing cytokines (IL-18, IL-33, IL-15, IFn-α, and IFn-γ) were tested in combination with EP to promote the production of T cells and Th1 cells differentiation, increasing antigen presentation and recruitment of dendritic cells [ 112 ].…”
Section: Electroporationmentioning
confidence: 99%
“…GET has been used for the delivery of cytokine genes for cancer immunotherapy. [ 104 ] For instance, GET has been used to deliver plasmid of interleukin 12 (IL‐12) into cancer cells for expressing IL‐12 protein, thereby realizing immunotherapy. [ 105 ] Daud et al first reported a clinical trial using IL‐12 DNA electroporation for the treatment of metastatic melanoma.…”
Section: Electricity Enables Antitumor Immunitymentioning
confidence: 99%